Complications of Intralesional Bleomycin in the Treatment of Orbital Lymphatic Malformations. (September 2014) - MacIntosh, Peter W.; Yoon, Michael K.; Fay, Aaron
Abstract Purpose: Lymphatic malformations (LM) are associated with significant morbidity, and in the orbit, can lead to vision loss. Treatment of these lesions is complicated by their infiltrative nature, making surgical excision challenging. Bleomycin has been used since the 1970s for sclerosis of LM to reduce the need for or improve the success of surgical excision. This paper reviews the complications associated with intralesional bleomycin in the treatment of orbital LM. Methods: A comprehensive literature search was performed on PubMed. Thirty full-length English articles were reviewed. Results: The pathophysiology and imaging characteristic of LM were first reviewed. The head and neck literature was heavily cited given the dearth of specific orbital data. This review highlights the common techniques and dosages for injection, the overall success rate of this treatment, and its common side effects. The orbital data were then reviewed, and differentiated from the head and neck literature. Conclusion: Sclerotherapy of most LM with bleomycin appears to be safe and effective, but the lack of specific orbital data means we must extrapolate LM data from other fields to orbital LM with caution. Additional research is warranted, though the risk-benefit ratio remains unknown.